Calving cycle of the Brunt Ice Shelf, Antarctica, driven by changes in ice-shelf geometry - De Rydt, Jan; Gudmundsson, Hilmar; Nagler, Thomas; Wuite, Jan (The Cryosphere, 2019)
Despite the potentially detrimental impact of large-scale calving events on the geometry and ice flow of the Antarctic Ice Sheet, little is known about the processes that drive rift formation prior to calving, or what controls the timing of these events. The Brunt Ice Shelf in East Antarctica presents a rare natural laboratory to study these processes, following the recent formation of two rifts, each now exceeding 50 km in length. Here we use a unique 50-years' time series of in-situ and remote sensing observations, together with numerical modelling, to reveal how slow changes in ice shelf geometry over time caused build-up of mechanical tension far upstream of the ice front, and culminated in rift formation and a significant speed-up of the ice shelf. These internal feedbacks, whereby ice shelves generate the very conditions that lead to their own (partial) disintegration are currently missing from ice flow models, which severely limits their ability to accurately predict future sea level rise.